Polyribosome binding of rabbit globin messenger RNA and messenger ribonucleoprotein labelled with bacteriophage-T4 RNA ligase and 5′-[(32)P] phosphocytidine 3′-phosphate - Thomas, N. Shaun B. (1983)
Rabbit polyribosomal globin messenger RNA (mRNA) and messenger ribonucleoprotein (mRNP) were labelled at the 3′ poly(A) tail to high specific activity with T4 RNA ligase and [5′-(32)P]pCp without consequent loss of functional activity. Labelled message was translated in both micrococcal nuclease treated and untreated rabbit reticulocyte lysates, as shown by the formation of labelled polyribosomes. The utilisation of labelled messenger was abolished by T2 toxin or sodium fluoride which are known to inhibit protein synthesis.